(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: In this paper considers the issues of using solar collectors as an alternative source of energy for territories remote from the power grids. One of the main criteria when choosing the solar collectors is the choice of the working fluid for heat transfer. Solar collectors according to the type of coolant are divided into a liquid and air. Materials and Methods: The solar collector works on the principle of energy transfer to a liquid from a source of radiant energy that is located a certain distance away, unlike conventional heat exchangers. In actual use, there are two types of solar collectors: one concentrates solar energy, the other doesn’t. Results: It is possible to give air clusters in places with low air temperature and low solar activity, and we use energy equations and their balances. Moreover, we have determined the thermal properties of solar clusters and useful energies. Conclusion: Climate characteristics and structures are crucial to the results of a solar array’s efficiency in covering ocean temperatures and the types of solar arrays to choose from with good results, heat fluxes and densities. In addition, we show that the solar collector is not considered a basic criterion in choosing the types of collectors. Key words: Solar energy, sustainable energy, low-radiation, solar collector, heat transfer